The Role of Social Media in Shaping Public Opinion and Its Influence on Economic Decisions - Ausat, Abu Muna Almaududi (Technology and Society Perspectives (TACIT), 2023)
Social media has become an integral part of modern society's daily life. With the rapid development of information and communication technology, social media platforms have changed the way people interact, share information, and express their views. The purpose of this study is to analyse the role of social media in shaping public opinion and its influence on economic decisions. This research uses a qualitative method. Data collection involved literature review and social media content analysis, focusing on opinion patterns and their influence. Reliability and validity were emphasised through triangulation and participation of secondary source participants in the analysis process. The study results show that in a digital age characterised by the central role of social media, it can be concluded that social media has a significant role in shaping public opinion and also influencing economic decision-making. Through social media, individuals and groups can interact with each other, share information, and participate in discussions that shape collective views on various issues.